Explorations on the antiviral potential of zinc and magnesium salts against chikungunya virus: implications for therapeutics - Davuluri, Kusuma Sai; Shukla, Shridhar; Kakade, Mahadeo; Cherian, Sarah; Alagarasu, Kalichamy; Parashar, Deepti (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Chikungunya virus (CHIKV), which causes chikungunya fever, is an arbovirus of public health concern with no approved antiviral therapies. A significant proportion of patients develop chronic arthritis after an infection. Zinc and magnesium salts help the immune system respond effectively against viral infections. This study explored the antiviral potential of zinc sulphate, zinc acetate, and magnesium sulphate against CHIKV infection.Methods: The highest non-toxic concentration of the salts (100 µM) was used to assess the prophylactic, virucidal, and therapeutic anti-CHIKV activities. Dose-dependent antiviral effects were investigated to find out the 50% inhibitory concentration of the salts. Entry bypass assay was conducted to find out whether the salts affect virus entry or post entry stages. Virus output in all these experiments was estimated using a focus-forming unit assay, real-time RT-PCR, and immunofluorescence assay.Results: Different time-and temperature-dependent assays revealed the therapeutic antiviral activity of zinc and magnesium salts against CHIKV. A minimum exposure of 4 hours and treatment initiation within 1 to 2 hours of infection are required for inhibition of CHIKV. Entry assays revealed that zinc salt affected virus-entry. Bypass entry assays suggested that both salts affected post-entry stages of CHIKV. In infected C57BL6 mice orally fed with zinc and magnesium salts, a reduction in viral RNA copy number was observed.The study results suggest zinc salts exert anti-CHIKV activity at entry and post entry stages of the virus life cycle, while magnesium salt affect CHIKV at post entry stages. Overall, the study highlights the significant antiviral potential of zinc sulphate, zinc acetate, and magnesium sulphate against CHIKV, which can be exploited in designing potential therapeutic strategies for early treatment of chikungunya patients, thereby reducing the virus-associated persistent arthritis.